2015
DOI: 10.1186/s13075-015-0557-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two hyaluronic acid formulations for safety and efficacy (CHASE) study in knee osteoarthritis: a multicenter, randomized, double-blind, 26-week non-inferiority trial comparing Durolane to Artz

Abstract: IntroductionIntra-articular injection of hyaluronic acid (HA) is often used as therapy for knee osteoarthritis because it is less expensive and less aggressive than total knee replacement. Therefore, it is important to document whether HA is safe and efficacious. We tested whether single and multiple injection viscosupplementation with HA is associated with clinically meaningful pain relief in a new randomized clinical trial (RCT). Our objective was to compare safety and efficacy of intra-articular HA in two f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 41 publications
(42 reference statements)
1
51
0
6
Order By: Relevance
“…Current therapeutic treatments, including weight reduction, physical exercise, physiotherapy, extra-articular devices, analgesics, opioids, non-steroidal anti-inflammatory drugs, corticoids, glucosamines (GlcNs), diacerein and hyaluronic acid (HA), can only treat symptoms, at best improving functionality and pain 8 . However, given the complexity of the pathology, these therapies are not curative 9 and arthroplasty still remains the only currently available treatment able to provide permanent pain relief and satisfactory function recovery when the final stages of OA are reached 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Current therapeutic treatments, including weight reduction, physical exercise, physiotherapy, extra-articular devices, analgesics, opioids, non-steroidal anti-inflammatory drugs, corticoids, glucosamines (GlcNs), diacerein and hyaluronic acid (HA), can only treat symptoms, at best improving functionality and pain 8 . However, given the complexity of the pathology, these therapies are not curative 9 and arthroplasty still remains the only currently available treatment able to provide permanent pain relief and satisfactory function recovery when the final stages of OA are reached 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely in our study, there was no difference in e cacy between these two types of HAs. In the study conducted by Zhang et al, [36] the therapeutic effectiveness of single injection of a cross-linked HMW-HA (Durolane) was compared to ve injections of a LMW-HA (Artz), showing that during a period of 26 weeks, Durolane was non-inferior to Artz in terms of pain, physical activity and knee-stiffness. Our study revealed a similar result within a period of same length.…”
Section: Discussionmentioning
confidence: 99%
“…In a few studies the e cacy of single cross-linked HMW-HA has been investigated, though there exists a discrepancy between them. [33][34][35][36] Our utilized HMW-HA (Arthromac®, Novatex Bioengineering SA Switzerland) is one of these cross-linked products which is indicated for single intra-articular injection in knee OA patients. [37] The aim of current trial was to compare the e cacy and safety of the single cross-linked HMW injection versus triple injection of low-molecular-weight IA-HA among knee OA patients in terms of function and pain improvement during a six-month period.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely in our study, there was no difference in efficacy between these two types of HAs. In the study conducted by Zhang et al, 44 the therapeutic effectiveness of single injection of a cross-linked HMW-HA (Durolane) was compared to five injections of a LMW-HA (Artz), showing that during a period of 26 weeks, Durolane was non-inferior to Artz in terms of pain, physical activity and knee-stiffness. 45 Our study revealed a similar result within a period of same length.…”
Section: Discussionmentioning
confidence: 99%
“…34 In a few studies, the efficacy of single cross-linked HMW-HA has been investigated, though there exists a discrepancy between them. [35][36][37][38] The aim of current trial was to compare the efficacy and safety of the single cross-linked HMW injection versus triple injection of low-molecular-weight IA-HA among knee OA patients in terms of function and pain improvement during a six-month period. Also, we aimed to determine the best IA-HA injection-protocol based on HA characteristics including molecular weight, cross-linkage and number of injections.…”
Section: Introductionmentioning
confidence: 99%